Comparison of measurement properties of three shortened versions of the balance evaluation system test (BESTest) in people with subacute stroke - Thitimard Winairuk; Marco Y.C. Pang; Vitoon Saengsirisuwan; Fay B. Horak; Rumpa Boonsinsukh (Medical Journals Sweden, 2019)
Objectives: To examine the reliability, validity and responsiveness of 3 different short versions of the Balance Evaluation Systems Test (BESTest: S--BESTest, Brief-BESTest and Mini-BESTest) in patients with subacute stroke. Design: A prospective cohort study. Participants: Patients with subacute stroke. Methods: Patients were assessed using the full BESTest. Scores of 3 short-form BESTests were later extracted. The intra-rater and inter-rater reliability (n = 12) were gathered from 5 raters. Concurrent validity was assessed with the Berg Balance Scale (BBS). Floor/ceiling effect, internal responsiveness and external responsiveness with the BBS (n = 70) were assessed at baseline, 2 weeks and 4 weeks post-rehabilitation. Results and conclusion: All short-form BESTests demonstrated excellent intra-rater and inter-rater reliability (intraclass correlation coefﬁcient (ICC) = 0.95-0.99) and excellent concurrent validity (r = 0.93-0.96). Unlike the Brief-BESTest and Mini-BESTest, the S-BESTest and BESTest had no significant floor/ceiling effects (< 20%). The standardized response mean of all 4 BESTest versions were large, ranging between 1.19 and 1.57, indicating sufficient internal responsiveness. The area under the curve of the S-BESTest and BESTest were significantly higher than the Brief-BESTest and Mini-BESTest, reflecting better accuracy of the S-BESTest and BESTest in identifying patients with subacute stroke who had balance improvement using the minimal clinically important difference of 6 and 16 points, respectively. These findings suggest that the S-BESTest is a short-form BESTest that is appropriate for assessing balance impairments in patients with subacute stroke.